The Impact of Remote Work on Job Stress and Job Satisfaction Among Employees During the COVID-19 Pandemic - Rahimah, Ghadah; Hooriya, Faadhillah; Muthmainnah, Syifa; Ananda, Rizky (PELNUS | Pen en Light for Natural Union of Science, 2025)
This research investigates the impact of remote work on job stress and job satisfaction among employees during the COVID-19 pandemic. As organizations rapidly transitioned to remote work in response to the pandemic, employees experienced both positive and negative effects on their work-related well-being. The study aims to explore how the shift to remote work influenced employees' levels of stress and job satisfaction, considering factors such as work-life balance, autonomy, social isolation, and communication challenges. Using a mixed-methods approach, data were collected through surveys and interviews from a diverse sample of employees working in various sectors. The findings reveal that while remote work enhanced job satisfaction by offering greater flexibility and autonomy, it also increased job stress due to blurred work-life boundaries and feelings of isolation. The study highlights the need for organizations to adopt flexible remote work policies that balance employee autonomy with adequate support systems to manage stress and maintain job satisfaction. These insights are critical for designing effective remote and hybrid work models that support employee well-being and productivity in future work environments.